Timing of ductile deformation and peak metamorphism in Skallevikshalsen, Lutzow-Holm Complex, East Antarctica - Kawakami,Tetsuo; Ikeda,Takeshi (National Institute of Polar Research, 2004)
P(論文) The geological structures of Skallevikshalsen, Lutzow-Holm Complex, East Antarctica are mainly controlled by two stages of ductile deformation, D_(m-1) and D_m. The D_(m-1) stage is characterized by the development of isoclinal F_(m-1) folds with fold axes gently plunging ENE or SWS, and axial planes parallel to the compositional layering (S_(m-1)) of the metamorphic rocks. The D_m stage is characterized by the development of tight folds with axes parallel to F_(m-1) and almost vertical axial planes. An axial planar foliation, S_m, defined by the alignment of biotite and hornblende, is formed in the hinges of F_m folds. No change in direction of elongation took place between D_(m-1) and D_m. Microstructural study and field observations show that a stretching lineation on S_(m-1) defined by the alignment of sillimanite was formed during D_(m-1). The alignment of sillimanite inclusions in garnet rims probably corresponds to an older schistosity formed during D_(m-2), which had a different orientation of principal strain axes than those of D_(m-1) and D_m. Peak metamorphic mineral assemblages are preserved in garnet cores, and their formation is considered to predate D_(m-2). Absence of the alignment of inclusions in garnet cores suggests that peak metamorphism was attained under conditions without strong deformation. departmental bulletin paper